2019
DOI: 10.1590/1519-6984.175350
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification and microbiological evaluation of isolates from equipments and food contact surfaces in a hospital Food and Nutrition Unit

Abstract: The hygienic and sanitary control in Food and Nutrition Units (FNU) is considered a standard procedure to produce adequate meals and reduce the risk of foodborne diseases and hospital infections. This study aimed to evaluate the isolation and identification of bacteria from equipment and food contact surfaces in a hospital FNU as well as to evaluate the sanitary condition. Likewise, it was analyzed the adhesion of the microorganisms on polyethylene cutting boards. The presence of aerobic mesophilic microorgani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 27 publications
0
5
1
7
Order By: Relevance
“…Regarding the utensils and food contact surfaces, the raw meats cutting boards were the most contaminated with a rate of 59.09%. This rate is still lower than that reported in a Brazilian hospital (90%) [ 28 ]. In fact, several studies demonstrated that these utensils present high microbial counts due to cross-contamination [ 29 ] and are influenced by the raw nature of handled materials and the surface material type (wood, stainless steel, plastic, etc.).…”
Section: Discussioncontrasting
confidence: 73%
“…Regarding the utensils and food contact surfaces, the raw meats cutting boards were the most contaminated with a rate of 59.09%. This rate is still lower than that reported in a Brazilian hospital (90%) [ 28 ]. In fact, several studies demonstrated that these utensils present high microbial counts due to cross-contamination [ 29 ] and are influenced by the raw nature of handled materials and the surface material type (wood, stainless steel, plastic, etc.).…”
Section: Discussioncontrasting
confidence: 73%
“…In this study, chicken meat had the highest prevalence of Y. enterocolitica due to slaughter the poultry outside the slaughterhouse under unhygienic condition, also high levels of bacterial contamination occur especially during defeathering and water chilling. further, elevate the contamination levels during evisceration of the carcasses, washing, and processing due to contamination by workers (Pieniz et al, 2019). On the other hand, the beef has the lowest percentage of isolates where the slaughter is done in a slaughterhouse of Mansoura city at Dakahlia Governorate, Egypt, showed lower contamination due to absence of section to slaughter pigs which are the carrier of Y. enterocolitica and excrete this bacterium in their feces (Paixão et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…É importante ressaltar que crianças, idosos, pacientes hospitalizados e imunocomprometidos são mais susceptíveis a adquirir DTAs, devido principalmente a alterações no sistema imunológico, assim as condições higiênico-sanitárias na produção de refeições e na higienização de utensílios utilizados na UAN, principalmente os de uso compartilhado entre os pacientes com enfermidades diferentes, precisam de uma maior atenção e cuidado devido a maior vulnerabilidade do públicoalvo (Hanzen et al, 2019;Pena et al, 2019;Pieniz et al, 2019).…”
Section: Discussionunclassified